Exploring the impact of the COVID-19 pandemic on perceptual disturbances and dysfunctional eating attitudes and behaviors: A review of the literature - Monthuy-Blanc, Johana; Corno, Giulia; Abou Chabake, Sara (Frontiers in Psychology, 2023)
From the outbreak of the novel coronavirus 2019 (COVID-19) a new physical and social distancing environment has changed our lives and, more particularly, the way of perceiving oneself, as well as eating attitudes and behaviours. An increasing number of studies have highlighted a risky scenario in terms of negative perceptions of one’s body as well as disordered eating and eating disorder patterns in both clinical and general population. With regard to this postulate, this literature review posits two main concepts – perceptual disturbances and dysfunctional eating attitudes and behaviours – in the general and (sub-)clinical populations, to provide an understanding of these phenomena during the COVID-19 pandemic. The main objective of this article is to provide a comprehensive and critical review of published scientific literature about perceptual disturbances (i.e., negative body image, body image disturbances, low body esteem) and dysfunctional eating attitudes and behaviours, including disordered eating (e.g., restrictive eating, binge-eating episodes, overeating, emotional eating) and eating disorders features in community (i.e., general population) and clinical and sub-clinical samples worldwide during the COVID-19 pandemic. The PubMed, ScienceDirect, Ebsco, and Google Scholar databases were searched. The initial search produced 42 references. Scientific publications from March 2020 to April 2022 were included, and among the works compiled, only published research articles have been retained. Purely theoretical papers were also excluded. The final selection consisted of 21 studies, covering both community, clinical (i.e., eating disorder population), and sub-clinical samples. The details of the results are discussed taking into consideration the potential impact of changes in the way we perceive ourselves and interact with others (e.g., the popularity of videoconferencing and the over-use of social network sites due to social isolation) as well as changes in eating attitudes and behaviours, physical activity and exercise (e.g., as an emotional response to the insecurity generated by the pandemic context), in community and (sub-)clinical samples. The discussion sheds light on two outcomes: (1) a summary of findings with methodological considerations; (2) an intervention continuum to deal with the consequences of the COVID-19 pandemic; (3) and a final conclusion.